The Importance of Auditory Learning in EFL Teaching: A Theoretical Perspective - Moses Adeleke Adeoye; Entika Fani Prastikawati (Universitas Pendidikan Ganesha, 2025)
This research explores the critical role of auditory learning strategies in enhancing language acquisition within English as a Foreign Language (EFL) education. Understanding diverse learning preferences becomes essential as the demand for effective language teaching methods grows. The study investigates the cognitive and communicative benefits of auditory learning strategies in improving language proficiency and learner engagement. Utilising a Thought Experiment Approach, the research synthesises insights from existing literature, theoretical frameworks, and hypothetical scenarios to examine the implications of auditory learning in EFL contexts. The findings indicate that auditory learning strategies significantly enhance listening and speaking skills, particularly for students who identify as auditory learners. Integrating technology, such as podcasts and interactive listening platforms, amplifies these benefits, making language learning more engaging and relevant. The importance of authentic listening experiences and constructive feedback in fostering communicative competence is also emphasised. In conclusion, the study highlights the transformative potential of auditory learning strategies in EFL education, advocating for their systematic incorporation into teaching practices. This research contributes to the existing literature by providing a conceptual framework that underscores the advantages of auditory learning strategies, promoting inclusivity and addressing educational inequities. This study enhances language acquisition outcomes and prepares learners for successful communication in a diverse global landscape by equipping educators with a deeper understanding of effective teaching methods.